Moda da natureza: inter-relações entre moda e biônica - Bertolini, Juliana (2009)
This research proposes a dialogue between Fashion and Bionics, pointing out new possible methodological, creative and conceptual practices so as to understand the meaning of Nature Fashion . The starting point is a social and historical contextualization of fashion in consumption society aiming at situating the environment of the proposed inter-relation (Fashion Bionic Design). Some important information about the meaning of Bionic Design and its possibilities applied to fashion skills will also be presented here. It is also the purpose of this research to raise some operating characteristics and fashion system openings to such inter-related dialogue. It is also intended to understand the meaning of Bionics and its changes along historical and technological development, so as to understand the project possibilities generated by the contact with nature and by the investigation of its environment. Parallels between concepts of Biology and of Design will be traced with the purpose of creating Design and Fashion hybrid concepts. New methodological forms of work as well as new possibilities of application in fashion and new operating forms in nature fashion field have been explored. Projects of some stylists, designers and artists have been showed in order to illustrate the project concepts explored in this research. This study also presents some information about the results of the field research in the Design and Material Selection Lab of the Federal University of Rio Grande do Sul at the time of the interview with Carmelo di Bartolo, Italian designer and Bionic researcher at the Design Innovation Institute, in Milan.